2015
DOI: 10.3389/fpls.2015.00077
|View full text |Cite
|
Sign up to set email alerts
|

The Epl1 and Sm1 proteins from Trichoderma atroviride and Trichoderma virens differentially modulate systemic disease resistance against different life style pathogens in Solanum lycopersicum

Abstract: Fungi belonging to the genus Trichoderma, commonly found in soil or colonizing plant roots, exert beneficial effects on plants, including the promotion of growth and the induction of resistance to disease. T. virens and T. atroviride secrete the proteins Sm1 and Epl1, respectively, which elicit local and systemic disease resistance in plants. In this work, we show that these fungi promote growth in tomato (Solanum lycopersicum) plants. T. virens was more effective than T. atroviride in promoting biomass gain, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
57
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(71 citation statements)
references
References 80 publications
(117 reference statements)
4
57
1
Order By: Relevance
“…tomato DC3000)42. These data indicate that MoSM1, like other CPs from both beneficial and pathogenic fungi4447, confers a broad-spectrum resistance against pathogens with different life styles in host and nonhost plants, providing a great potential for application of MoSM1 in genetic improvement of disease resistance in other crop plants. The MoSM1-OE plants did not show a decreased resistance against sheath blight disease, although they did not gain an increased resistance (Fig.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…tomato DC3000)42. These data indicate that MoSM1, like other CPs from both beneficial and pathogenic fungi4447, confers a broad-spectrum resistance against pathogens with different life styles in host and nonhost plants, providing a great potential for application of MoSM1 in genetic improvement of disease resistance in other crop plants. The MoSM1-OE plants did not show a decreased resistance against sheath blight disease, although they did not gain an increased resistance (Fig.…”
Section: Discussionmentioning
confidence: 83%
“…Indeed, a number of CPs from different filamentous fungi, e.g. SM1, SM2 and Epl1 from the biocontrol agents T. virens and T. atroviride 37404547 as well as BcSpl1 from B. cinerea and a CP from C. platani 2944, were shown to induce both local and systemic disease resistance in host and nonhost plants against different life style pathogens. In the present study, we found that overexpression of MoSM1 in transgenic rice plants confers an improved resistance against two strains representing difference races of M. oryzae and Xoo , as revealed by reduced disease severity and suppressed in planta pathogen growth (Figs 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Salas‐Marina et al . () reported that Sm1 and eliciting plant response‐like protein 1 (Epl1), secreted by T. virens and T. atroviride , induced resistance against Alternaria solani , B. cinerea and P. syringae pv. tomato in tomato.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptional analysis of downy mildew resistance induced by Trichoderma harzianum T39 in susceptible grapevines showed complex transcriptional reprogramming resulting in enhanced expression of PAL, PPO, PR-1 and PR-5 genes31. The transcripts of glucanase and POX enzymes and PR-5 were significantly enhanced during of Trichoderma atroviride and Trichoderma virens secretory proteins mediated resistance against Alternaria solani, Botrytis cinerea and Pseudomonas syringae 32. In tomato, Trichoderma hamatum 382 induced resistance against Xanthomonas vesicatoria in tomato and Botrytis cinerea in Arabidopsis thaliana correlated with enhanced expression of PR-5 genes67.…”
Section: Discussionmentioning
confidence: 99%